Answer:
![\textsf{Inverse function}: \quad f^(-1)(x)=(3)/(4)-(3)/(10)x](https://img.qammunity.org/2023/formulas/mathematics/high-school/qc5c96w7ufa7sdpnwgqk0rw2lnmyu2d727.png)
![x\textsf{-intercept}:\quad\left((5)/(2),0\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/aqjtxyrrv36o41beokau4rwwbfyi67nop7.png)
Explanation:
Given:
![f(x)=2(1)/(2)-3(1)/(3)x](https://img.qammunity.org/2023/formulas/mathematics/high-school/5c7utnys37rxs1sncmdfu88xwqy5owiftu.png)
Rewrite the function so it is a rational function
Convert the mixed numbers to improper fractions:
![\implies f(x)=(5)/(2)-(10x)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/u3y4l9re3ng8jphvn639i5zpnxq54xgc78.png)
Make the denominators the same:
![\implies f(x)=(3 \cdot 5)/(3\cdot 2)-(2 \cdot 10x)/(2 \cdot 3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/2wrf6cybt6r72g1i7hcv91rhuy7p8zhazn.png)
![\implies f(x)=(15)/(6)-(20x)/(6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/6iviyyxcm9i8ifq5n5fmcgh8tggt7oipfq.png)
Combine:
![\implies f(x)=(15-20x)/(6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/9z8gahlkkye0b651y53in1gjp1p6d6xldb.png)
The inverse of a function is its reflection in the line y = x
To find the inverse, make x the subject
Replace f(x) with y:
![\implies y=(15-20x)/(6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/corjgn5nwpb0dryk54pprwqoovauxnxkoa.png)
![\implies 6y=15-20x](https://img.qammunity.org/2023/formulas/mathematics/high-school/qsdha5dv81tsbkbohxs7izoewhikdd1w3r.png)
![\implies 6y-15=-20x](https://img.qammunity.org/2023/formulas/mathematics/high-school/rsca00dnnmj93gblyl63goufj0uttz18iu.png)
![\implies x=(-6y+15)/(20)](https://img.qammunity.org/2023/formulas/mathematics/high-school/t52s48yxw5bozvx426t2muqo8i2wb7mogi.png)
![\implies x=(15-6y)/(20)](https://img.qammunity.org/2023/formulas/mathematics/high-school/bpqiljbflen7q8rel8sooz1lax71mv5gqo.png)
Replace x with
and y with x:
![\implies f^(-1)(x)=(15-6x)/(20)](https://img.qammunity.org/2023/formulas/mathematics/high-school/olpbaz6xojxbav375ho63rjtmy0u2j1a1d.png)
If necessary, convert back into the same format as the original function:
![\implies f^(-1)(x)=(15)/(20)-(6x)/(20)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4rohplh3igdrzjvn6gmlpr60lamp3tj5fa.png)
![\implies f^(-1)(x)=(3)/(4)-(3)/(10)x](https://img.qammunity.org/2023/formulas/mathematics/high-school/1mmolq7p5auqunbwagogmso9sjpm0d5lsx.png)
The x-intercept of the inverse function is the point at which it crosses the x-axis, so when
![f^(-1)(x)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/fxlbkeu5yhpa97j5xj4agrjoz14qcwyu1d.png)
![\implies (15-6x)/(20)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/j7esubid2moie6dy1a1v35s8n2114ntbrb.png)
![\implies 15-6x=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/o7keqn6o4oj3du4tqnia45h9o4ekmbwgmx.png)
![\implies 6x=15](https://img.qammunity.org/2023/formulas/mathematics/high-school/h6qd8sqy50qofm689yqfydm1lmr7yumb8u.png)
![\implies x=(15)/(6)=(5)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/me0be4xzq5f51licjl7puz1uxz8g9rc4fb.png)
Therefore, the x-intercept is:
![\left((5)/(2),0\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/3tqebf38s09yu29v8l1uj3d5cu0lny6gez.png)